Essential Roles of the Linker Sequence Between Tetratricopeptide Repeat Motifs of Ethylene Overproduction 1 in Ethylene Biosynthesis - An, Chuanjing; Gao, Yuefang (Frontiers in Plant Science, 2021)
Ethylene Overproduction 1 (ETO1) is a negative regulator of ethylene biosynthesis. However, the regulation mechanism of ETO1 remains largely unclear. Here, a novel eto1 allele (eto1-16) was isolated with typical triple phenotypes due to an amino acid substitution of G480C in the uncharacterized linker sequence between the TPR1 and TPR2 motifs. Further genetic and biochemical experiments confirmed the eto1-16 mutation site. Sequence analysis revealed that G480 is conserved not only in two paralogs, EOL1 and EOL2, in Arabidopsis, but also in the homologous protein in other species. The glycine mutations (eto1-11, eto1-12, and eto1-16) do not influence the mRNA abundance of ETO1, which is reflected by the mRNA secondary structure similar to that of WT. According to the protein-protein interaction analysis, the abnormal root phenotype of eto1-16 might be caused by the disruption of the interaction with type 2 1-aminocyclopropane-1-carboxylic acid (ACC) synthases (ACSs) proteins. Overall, these data suggest that the linker sequence between tetratricopeptide repeat (TPR) motifs and the glycine in TPR motifs or the linker region are essential for ETO1 to bind with downstream mediators, which strengthens our knowledge of ETO1 regulation in balancing ACSs.